Fertilization Rate and Number of Embryos on Day 2 after Intrauterine and Deep Intrauterine Insemination Using Frozen-Thawed Boar Semen in Multiparous Sows - Kakanang Buranaamnuay; Yodchai Panyaboriban; Padet Tummaruk; Mongkol Techakumphu (Veterinary Medicine International)
The present study determines fertilization rate and number of embryos on Day 2 after intrauterine insemination (IUI) and deep intrauterine insemination (DIUI) using frozen-thawed (FT) boar semen in multiparous sows. Twelve crossbred Landrace × Yorkshire multiparous sows were included. The sows were inseminated at 24 h after oestrus detection and reinseminated every 12 h until ovulation took place. The inseminations were conducted using IUI with 2×109 FT sperm per dose (n=6) and DIUI with 1×109 FT sperm per dose (n=6). The sows were slaughtered at 45.1±7.2 h after ovulation. Embryos and unfertilized oocytes were flushed from the oviducts. IUI yielded a better fertilization rate than DIUI (66.0% versus 31.0%, P<.001). The number of embryos was 13.5±2.7 and 6.6±3.2 embryos/sow in IUI and DIUI groups, respectively (P=.08). The proportion of sows having unilateral fertilization was higher in the DIUI (3/5) than the IUI group (1/6). In conclusion, IUI with at least 2×109 total number of FT boar spermatozoa is recommended.